Field Grafting Studies in Pinus patula - Kapoor, M. L.; Vakshasya, R. K.; Kedharnath, S. (Indian Forester, 1977)
Pinus patula is a fast growing exotic species from eastern Mexico which has done well in sub-tropical regions of India. It is a valuable long fibred raw material for paper pulp. The seeds of this species are in great demand by many countries for afforestation purposes. Thus, for ensuring sufficient production of genetically improved seeds of this species within the country, it was considered essential to establish clonal seed orchards. A knowledge of the optimal time for grafting is a very important prerequisite for speedy establishment of clonal seed orchards. To obtain information on the optimum time for grating, a systematic trial on field grafting was carried out from the month of September, 1975 to June, 1976 at New Forest, Dehra Dun. One hundred percent success in graft establishment was achieved during the months of November 1975 to March 1976. The grafting carried out in the months of September, October and April gave success in establishment that varied from 50 to 80 percent. The grafting carried out during May and June failed to establish. The climatic conditions obtaining during November to March with 11.4 to 16.8Â°C mean temperature appeared to be very conducive for establishment of the grafts. During the months of May and June when the mean temperature was 24.8 and 26.3Â°C the grafts failed to establish. Presumably, such high temperatures are not conducive for graft establishment.